(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This research examined the perceived influence of guidance and counselling on sexual health awareness among students in Rivers State University. The study was guided by two research questions and two hypotheses. A descriptive survey design was adopted. The population comprised male and female students of Rivers State University, with a sample size of approximately 1,200 students selected through stratified random sampling based on a 30% sampling rate. Data were collected using a self-structured questionnaire titled "Perceived Influence of Guidance and Counselling on Sexual Health Awareness (PIGC-SHA)." The reliability of the instrument was confirmed using Cronbach’s Alpha, yielding coefficients between 0.82 and 0.89, indicating good internal consistency. Mean and standard deviation were used to analyze the research questions, while independent samples t-tests tested the hypotheses at a 0.05 level of significance. Findings revealed that guidance and counselling significantly enhanced students’ awareness of sexual health, promoting safer sexual behaviors and informed decision-making. However, gaps such as limited accessibility to counselling services and occasional stigma were identified. The study recommended expanding guidance and counselling programs, increasing awareness campaigns, and improving accessibility to sexual health resources on campus. In conclusion, guidance and counselling played a critical role in improving sexual health awareness among students in Rivers State University.